Did Ranchers and Slaughterhouses Respond to Zero‐Deforestation Agreements in the Brazilian Amazon?. Issue 1 (12th May 2015) - Gibbs, Holly K.; Munger, Jacob; L'Roe, Jessica; Barreto, Paulo; Pereira, Ritaumaria; Christie, Matthew; Amaral, Ticiana; Walker, Nathalie F.
Abstract: New supply chain interventions offer promise to reduce deforestation from expansion of commercial agriculture, as more multinational companies agree to stop sourcing from farms with recent forest clearing. We analyzed the zero‐deforestation cattle agreements signed by major meatpacking companies in the Brazilian Amazon state of Pará using property‐level data on beef supply chains. Our panel analysis of daily purchases by slaughterhouses before and after the agreements demonstrates that they now avoid purchasing from properties with deforestation, which was not the case prior to the agreements. Supplying ranchers registered their properties in a public environmental registry nearly 2 years before surrounding non‐supplying properties, and 85% of surveyed ranchers indicated that the agreements were the driving force. In addition, supplying properties had significantly reduced deforestation rates following the agreements. Our results demonstrate important changes in the beef supply chain, but the agreements' narrow scope and implementation diminish outcomes for forest conservation.